Applying the Think-Aloud Method for Usability Analysis in the Peking Metagamelan Virtual Reality Learning Application - Patricia Meta Pudya Astari; Clara Hetty Primasari; Djoko Budiyanto Setyohadi; Yohanes Priadi Wibisono; Mutiara Cininta (Indonesian Journal of Information Systems, 2023)
The rapid development of technology affects people’s lives, including education, and virtual reality is one of many digital learning media that can be useful for learning. Virtual reality allows users to interact with the environment through a virtual world. With this concept in mind, an application to support gamelan learning based on Virtual Reality was developed called Peking Metagamelan Virtual Reality. Peking is a gamelan instrument made of bronze with rectangular blades. This application needs to know the user’s opinion regarding its performance and usability in its development. Therefore, the Think-aloud method assisted in the usability analysis process in the VR Metagamelan Peking application. The Think-aloud approach helps to express what the user feels and thinks when using the application. The research process involved five respondents from various educational backgrounds and different experiences. Respondents were asked to work on several task scenarios that were ordered. During the task scenario, respondents were asked to convey their thoughts regarding the application they were trying. The results were then analyzed and produced some recommendations for further improvements to the VR Metagamelan Peking application. The recommendations included improving the application interface, adding several features, and reducing the character’s speed.